2014
DOI: 10.5194/amt-7-4491-2014
|View full text |Cite
|
Sign up to set email alerts
|

Middle-atmospheric zonal and meridional wind profiles from polar, tropical and midlatitudes with the ground-based microwave Doppler wind radiometer WIRA

Abstract: Abstract. WIRA is a ground-based microwave Doppler spectroradiometer specifically designed for the measurement of profiles of horizontal wind in the upper stratosphere and lower mesosphere region where no other continuously running measurement technique exists. A proof of principle has been delivered in a previous publication. A technical upgrade including a new high-frequency amplifier and sideband filter has improved the signal to noise ratio by a factor of 2.4. Since this upgrade the full horizontal wind fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 27 publications
(33 reference statements)
5
86
0
Order By: Relevance
“…Measurements by such a system achieve a single-sideband noise temperature of 200 K and a total system temperature of 1400 K. We also assess how wind measurements would be improved by using radiometers with system temperatures of 700 and 1000 K. Spectral analysis of the down-converted signal over a 300 MHz bandwidth, centred on the emission line(s) of interest, and with channel widths ≥10 kHz is based on the specifications of commercially available chirp transform and fast Fourier transform (FFT) spectrometers for radiofrequency (RF) analysis. Rüfenacht et al (2014) showed for the WIRA instrument that frequency errors arising from reference oscillator instabilities and spectrum baseline artefacts such as standing waves are either small or can be adequately characterised to minimise their impact on the wind retrievals. However for other wind radiometers these effects could make a larger contribution to the measurement uncertainty that is not considered in the simulations here.…”
Section: Ground-based Radiometer Instrument and Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements by such a system achieve a single-sideband noise temperature of 200 K and a total system temperature of 1400 K. We also assess how wind measurements would be improved by using radiometers with system temperatures of 700 and 1000 K. Spectral analysis of the down-converted signal over a 300 MHz bandwidth, centred on the emission line(s) of interest, and with channel widths ≥10 kHz is based on the specifications of commercially available chirp transform and fast Fourier transform (FFT) spectrometers for radiofrequency (RF) analysis. Rüfenacht et al (2014) showed for the WIRA instrument that frequency errors arising from reference oscillator instabilities and spectrum baseline artefacts such as standing waves are either small or can be adequately characterised to minimise their impact on the wind retrievals. However for other wind radiometers these effects could make a larger contribution to the measurement uncertainty that is not considered in the simulations here.…”
Section: Ground-based Radiometer Instrument and Locationmentioning
confidence: 99%
“…Comparison of their measured time series from four locations at polar, mid-, and tropical latitudes with ECMWF model data showed that meridional and zonal stratospheric winds agreed to within 10 %. However in the mesosphere, above 40-50 km, observed and modelled zonal wind speeds differ significantly by up to 50 % (Rüfenacht et al, 2014 (Hibbins et al, 2006(Hibbins et al, , 2009Nielsen et al, 2012). These observations have been limited to the troposphere, lower stratosphere, and upper mesosphere; co-located radiometric measurements could provide complementary observations filling the gap in altitudes at 25-75 km.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the determination of wind profiles the Doppler shifts of signals from opposite azimuths in 68 • off-zenith direction are compared. The retrieval algorithm which is based on the optimal estimation 15 method (Rodgers, 2000) is similar to the version in Rüfenacht et al (2014) with a constant zero wind a priori profile. In this study we use identical a priori standard deviations for both horizontal wind components equivalent to 4 times the standard deviation of 6 years of zonal wind data from ECMWF.…”
mentioning
confidence: 99%
“…The trustworthy altitude range, i.e. where the measurement response is > 0.8, the altitude resolution is < 20 km and the altitude accuracy is < 4 km (for details see Rüfenacht et al, 2014), typically extends 25 from 7 to 0.03 hPa (∼ 35 to 70 km). Microwave radiometers can be highly automatised and have the ability to pursue the measurements during overcast conditions what leads to near-continuous time series of observations, a characteristic that will be exploited for the model validations during almost a full annual cycle presented in Sect.…”
mentioning
confidence: 99%